Highly Sensitive Refractive Index Sensor Based on Dual Peak Plasmonic Tapered D-shaped PM-PCF Coated with Gold Nano-Structures - Hindal, Suaad S.; Al-Bawai, Zainb F.; Mahmood, Aseel I. (Iraqi Journal of Laser, 2025)
his paper uses the finite element method (FEM) to study a Surface Plasmon Resonance (SPR) refractive index sensor based on D-shaped Polarization Maintain Photonic Crystal Fiber (PM-PCF). A chemically stable plasmonic material, gold (Au), with hemispherical structures having a radius of 50 nm, is applied to the surface of a D-shaped sensor to create the surface plasmon resonance (SPR) effect, enabling this SPR sensor to detect variation in the surrounding analyte refractive index (RI). The resonance condition will change when the refractive index of the targeted analyte changes, leading to a certain shift in the loss peak. Two resonant peaks are observed, one located in the visible part of the spectrum, and the second in the near-infrared region.Our suggested design offers a high wavelength sensitivity (WS) of 5176 nm/RIU and the spectral resolution for this sensor is 1.93 x 10-5RIU, for y-polarization. For x-polarization, the wavelength sensitivity of the 1st and 2nd peaks are 1058 nm/RIU and 3764 nm/RIU, respectively. The spectral resolution for the 1st and 2nd peaks is 9.45x 10-5RIU and 2.65x 10-5RIU, respectively in the high sensing range of 1.34 to 1.41 RIU. The results show that this improves the sensor’s ability to detect the refractive index. The proposed SPR sensor designhas high sensitivity, high resolution, and high linearity, a promising result that could be used in environmental monitoring, biological detection, physical sensors, and chemical analysis.